Jonge kunst uit de collectie Dotremont - Brussel. - Tapié, Michel; Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum Eindhoven, 1960)
Albers, Josef ; Alechinsky, Pierre ; Appel, Karel ; Applebey, Theodore ; Arp, Hans (Jean) ; Baj, Enrico ; Bazaine, Jean ; Bertrand, Gaston ; Brown, James ; Burri, Alberto ; Capogrossi, Giuseppe ; Consagra, Pietro ; Corneille ; Crippa, Alberto ; Damian, Horia ; Degottex, Jean ; Dubuffet, Jean ; Dumitresco, Natalie ; Falkenstein, Claire ; Fautrier, Jean ; Fontana, Lucio ; Francis, Sam ; Francken, Ruth ; Giacometti, Alberto ; Gottlieb, Adolph ; Guiette, René ; Guston, Philip ; Hantaï, Simon ; Van Hoeydonck, Paul ; Imaï, Toshimitsu ; Istrati, Alexander ; Jorn, Asger ; Kelly, Ellsworth ; Kline, Franz ; de Kooning, Willem ; Loubchansky, Marcelle ; Manessier, Alfred ; Mathieu, Georges ; Mesens, E.L.T. ; Messagier, Jean ; Moreni, Mattia ; Mortier, Antoine ; Motherwell, Robert ; Pignon, Edouard ; Plaubert, Jean ; Poliakoff, Serge ; Pollock, Jackson ; Riopelle, Jean Paul ; Rothko, Mark ; Sallès, Francis ; Schneider, Gérard ; Serpan, Jaroslaw ; Soulages, Pierre ; Tal-Coat, Pierre ; Tàpies, Antoni ; Teshigahara, Sofu ; Tobey, Mark ; Ubac, Raoul ; Vasarely, Victor ; van Velde, Bram
biog. [15 p.]
Nederlands
Nederlands & Frans
Jonge kunst uit de collectie Dotremont - Brussel, Van Abbemuseum Eindhoven, 20.02.1960 - 27.03.1960
boek